Behaviour of reinforced structures under simulated toe scouring. Issue 4 (August 2012) - Huang, C.-C.; Chen, Y.-S.
Abstract : ABSTRACT: Four geosynthetic-reinforced model walls backfilled with an idealised two-dimensional uniform medium were built and brought to failure using surcharging and toe cutting to simulate the behaviour of waterfront structures subjected to potential slope toe scouring. External stability analyses – base sliding, overturning, and bearing capacity failure – were performed in order to examine their relevance to the displacement, and ultimate failure state, of the walls. It was shown that a well-designed geosynthetic-reinforced wall can sustain a surcharge and a uniform toe cut up to an equivalent wall height ( H e ) equal to 1.4 times the total wall height ( H t ) with negligible horizontal and vertical wall displacement. This can be attributed to the effective mobilisation of tensile force in the reinforcement layers. Safety factors for base sliding and overturning vary within small and acceptable ranges during this stage. However, a drastic increase in wall displacement occurred during ground cutting adjacent to the toe of the tested wall, owing to insufficient bearing capacity beneath the wall. This increase was associated with a rapid decrease in the safety factor against bearing capacity failure beneath the wall. Detailed internal and external stability analyses for the wall behaviour observed here are reported in a companion paper.